Culturally Contextualized Implementation of Applied Behavior Analysis for Children with Autism Spectrum Disorder: Evidence from a Therapy Center in Banjarmasin - Nisa, Uswatun; Hayati, Firdha (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2025)
Applied Behavior Analysis (ABA) is widely recognized as an evidence-based intervention for children with autism spectrum disorder (ASD). However, limited research has examined how ABA practices are implemented and adapted within local cultural and educational contexts in developing countries. This study investigates the implementation of ABA-based educational treatment for children with ASD at a therapy center in Banjarmasin, Indonesia, with particular attention to its potential relevance for inclusive school practices. A qualitative descriptive design was employed. Data were collected through classroom observations, semi-structured interviews, and document analysis involving therapists, parents, and children with ASD. The analysis focused on identifying key therapeutic practices and examining how core ABA principles are operationalized within daily intervention routines. The findings indicate that therapists consistently apply several fundamental ABA principles, including structured instruction, behavioral shaping, repetition, reinforcement, and consistency. These practices contribute to improvements in children’s self-help abilities, emotional regulation, and social interaction skills. Furthermore, the therapeutic strategies demonstrate potential for adaptation in inclusive educational settings, where teachers can incorporate simplified ABA-based techniques to support behavioral and learning development among autistic students. This study contributes to the literature by providing empirical evidence on the culturally contextualized implementation of ABA in therapy services in Indonesia. The findings highlight the importance of therapist–parent collaboration and suggest that culturally adapted ABA practices can support the inclusion of children with ASD in mainstream educational environments.